The Effect of Corporate Diversification, Customer Concentration on Tax Avoidance in Indonesia - Aryotama, Putra; Firmansyah, Amrie (Jurnal Akuntansi dan Bisnis, 2019)
This study aims to examine the effect of corporate diversification, customer concentration on tax avoidance in Indonesia’ Non-Financial Companies. Companies diversify because of the private benefits managers receive from diversifying. Also, Companies may choose to have only a few customers to create a close relationship with those customers. Meanwhile, tax avoidance is a reduction in corporate tax liability, which is conducted by the company legally. This study employs a quantitative method using linear regression analysis and uses panel data of companies listed under the Indonesian Non-Financial Companies on IDX from 2014 to 2017. Based on purposive sampling was conducted, the total number of observations is 483 firm-year. The results of this study suggest that corporate diversification and customer concentration are positively associated with tax avoidance.